STUDENTS PERCEPTION TOWARD ENGLISH FOR SPECIFIC PURPOSES IMPLEMENTATION IN STIE BINA KARYA DURING THE PANDEMIC - Haya Haratikka; Dedy Dwi Arseto (Proceeding International Seminar of Islamic Studies, 2021)
The spread of Covid-19 in Indonesia has paralyzed almost in all system in our live. It significantly affect education system in all over the world. The physical distancing emerge in order to stop the covid 19 transmission.Teachers have to set the way of learning for students on several learning platforms so students can learn effectively and attractively to prevent the boredom at home. No exception for learning English for Specific Purposes. This study is going to describe students perception in the implementation of English for Specific Purposes in STIE Bina Karya during the pandemic. This study applied the descriptive qualitative approach which took the data from 108 informants from students who had taken two semesters in pandemic situation. The result of this study were the ESP implementation during the pandemic did not run 100%. Only two from four skills were assessed by the lecturer through the Google Classroom and Youtube Channel. But so far, the informants/the students were still enjoyed learning ESP even in online class. Keywords: pandemic, ESP, perception